Immune Dysfunction in Rett Syndrome Patients Revealed by High Levels of Serum Anti-N(Glc) IgM Antibody Fraction - Anna Maria Papini; Francesca Nuti; Feliciana Real-Fernandez; Giada Rossi; Caterina Tiberi; Giuseppina Sabatino; Shashank Pandey; Silvia Leoncini; Cinzia Signorini; Alessandra Pecorelli; Roberto Guerranti; Solange Lavielle; et al. (Journal of Immunology Research)
Rett syndrome (RTT), a neurodevelopmental disorder affecting exclusively (99%) female infants, is associated with loss-of-function mutations in the gene encoding methyl-CpG binding protein 2 (MECP2) and, more rarely, cyclin-dependent kinase-like 5 (CDKL5) and forkhead box protein G1 (FOXG1). In this study, we aimed to evaluate the function of the immune system by measuring serum immunoglobulins (IgG and IgM) in RTT patients (n=53) and, by comparison, in age-matched children affected by non-RTT pervasive developmental disorders (non-RTT PDD) (n=82) and healthy age-matched controls (n=29). To determine immunoglobulins we used both a conventional agglutination assay and a novel ELISA based on antibody recognition by a surrogate antigen probe, CSF114(Glc), a synthetic N-glucosylated peptide. Both assays provided evidence for an increase in IgM titer, but not in IgG, in RTT patients relative to both healthy controls and non-RTT PDD patients. The significant difference in IgM titers between RTT patients and healthy subjects in the CSF114(Glc) assay (P=0.001) suggests that this procedure specifically detects a fraction of IgM antibodies likely to be relevant for the RTT disease. These findings offer a new insight into the mechanism underlying the Rett disease as they unveil the possible involvement of the immune system in this pathology.